Guest lecture series department – based - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2021)
Dr Hamizah Mohd Zaki had been appointed as a guest lecturer in the Department of Materials and Metallurgical Engineering Lecture Series, Faculty of Industrial Technology and Systems Engineering, ITS, Surabaya Indonesia, on 25 June 2021. The theme of the virtual talk was "The Root of Surface Engineering", under Heat Treatment and Surface Engineering course.